Kolaborasi Dinasti Islam Abbasiyah dengan Kerajaan Katolik Franka pada Abad ke-8 M - Purnama, Agung (Historia Madania: Jurnal Ilmu Sejarah, 2024)
The portrait of the interaction between Islam and the West (Christianity) is often narrated in a confrontational form. These two civilizations are often positioned as polar opposites. A series of conflicts both in the past such as the Crusades, or other conflicts in the contemporary era, have brought traumatic feelings and protracted mutual suspicion between the two. However, is it true that the relationship between Islam and the West is just a conflict? Is there a cooperative relationship between the political institutions of the Islamic and Christian worlds in history? This study uses historical methods consisting of heuristics, criticism, interpretation, and historiography, as well as literature study techniques. From the results of the research, it was found that in the 8th century AD, the Abbasid dynasty had established cooperation with the Frankish Empire. The exchange of gifts and ambassadors symbolized the friendship between Caliph Harun Ar-Rashid and King Charlemagne. Politically, Caliph Harun Ar-Rashid supported Charlemagne to disrupt the existence of his fellow Muslim rivals, namely the Umayyad dynasty II in Andalusia. On the other hand, Charlemagne supported Harun Ar-Rashid in his conflict with the Byzantine Empire, the rival of the Frankish Empire among Christians. From these conditions, it can be concluded that at certain moments the Islamic world and the West can interact in a harmonious spectrum. This collaborative condition is also present in historical fragments, which are important to be narrated amidst the domination of confrontational historical narratives.